EKSPLORASI GESTUR SISWA DAN KEMAMPUAN PENYELESAIAN SOAL CERITA PENALARAN TINGKAT TINGGI PADA OPERASI BILANGAN - Andi Aswani; Rukli; Erwin Akib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study explores the relationship between students' gestures and their high-level reasoning mathematical problem-solving abilities presented in the form of stories. It is quantitative research with a correlational approach. The research population consists of 30 fourth-grade students. The data collection instruments used were observation sheets and the PTT problem-solving test. The data analysis employed descriptive analysis, Classical Assumption Test, and Pearson correlation. The research results indicate significant findings, suggesting a relationship between students' gestures and their PTT mathematical problem-solving abilities, and the relationship between the two variables is negative